Application effect of BOPPPS teaching model on fundamentals of nursing education: a meta-analysis of randomized controlled studies - Li, Yue; Li, Xiao; Liu, Yan; Li, Yang (Frontiers in Medicine, 2024)
Background: BOPPPS (bridge-in, learning objective, pretest, participatory learning, posttest, and summary) is a student-centered, closed-loop teaching model that emphasizes real-time communication and feedback. Objectives: This study aimed to review and evaluate the effect of the BOPPPS teaching model in "Fundamentals of Nursing" teaching. Methods: A meta-analysis of randomized controlled trials (RCTs) based on the BOPPPS teaching model in "Fundamentals of Nursing" teaching was conducted. Domestic and foreign databases were searched for the period 2010 to September 2023. Thirteen RCTs were included, and teaching outcomes were measured and analyzed. Two researchers independently identified, selected, and extracted data from the studies and examined the risk of bias. Primary outcomes: Students' exam scores, including theoretical scores (reflecting understanding of course content) and practical scores (evaluating practical skills); Secondary outcomes: Self-learning ability score (measuring self-directed learning ability) and satisfaction rate of teaching effect (students' overall satisfaction with teaching). The results were evaluated using the Grading of Recommendations, Assessment, Development, and Evaluations (GRADE) profiler software. Results: A total of 2991 nursing students from 13 studies were included, with 1465 students in the BOPPPS teaching group and 1526 students in the traditional teaching group. The BOPPPS teaching model showed significantly higher scores in theoretical score (MD=3.35, 95% CI: 2.35-4.35, Z = 6.56, P < 0.00001), practice score (MD=4.50, 95% CI: 1.95-7.05, Z = 3.45, P = 0.0006), and self-learning ability score (MD=6.76, 95% CI: 5.38-8.14, Z = 9.60, P < 0.00001) compared to the traditional teaching group. The satisfaction rate of students in the BOPPPS teaching group regarding teaching effectiveness was 89% (95% CI=0.84-0.93). The differences were statistically significant (P < 0.05). The GRADE evidence level for theoretical score and satisfaction rate of teaching effect is low, for practice score is very low, and for self-learning ability score is moderate. Conclusion: The BOPPPS teaching model is beneficial in improving theoretical scores, practice scores, and self-learning ability scores in "Fundamentals of Nursing" and enhancing student satisfaction with the teaching effect. The teaching effect is superior to the traditional teaching method.